Equity incentives and firm performance: The mediating role of investment efficiency under executives’ political identity - Zhao Zeyi; Junainah Jaidi; Debbra Toria Nipo (Environment and Social Psychology, 2025)
Investment inefficiency remains a critical obstacle to firm performance in China, raising questions about how managerial incentives and political identity shape executive decision-making. Agency, expectancy, and social identity theories jointly suggest that equity incentives may align managerial and shareholder interests, encourage prudent investment decisions via effort–reward considerations, and that executives’ political identity may reinforce long-term oriented investment behaviour. Building on these theories, this study examines how equity incentives influence firm performance through investment efficiency, and how executives’ political identity moderates this relationship. Using a panel dataset of Chinese listed firms, the empirical results show that equity incentives improve firm performance by approximately 8%, with investment efficiency functioning as a key mediating channel. In addition, executives’ political identity, as reflected by Communist Party membership of China, positively moderates this relationship, further reinforcing the effectiveness of equity incentives. Overall, the findings highlight investment efficiency as a behavioural mechanism linking equity incentives to firm performance, demonstrate the reinforcing role of executives’ political identity, and contribute to governance research by integrating psychological insights while offering practical guidance for designing effective managerial incentive schemes in emerging markets.